Silicon-based negative electrode material and preparation method thereof, dry electrode, battery and electric equipment
By adopting a silicon-based negative electrode material with a core-shell structure, the ion-conducting but non-electronic conduction characteristics and three-dimensional mesh structure of the crosslinked polymer layer are solved, and the electrode performance degradation caused by PTFE side reaction and volume expansion of the silicon-based material is achieved, and the excellent first discharge capacity, first effect and cycling performance of the battery are achieved.
Patent Information
- Application Number
- CN202411716401.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
When the existing dry electrodes use silicon-based materials as the negative electrode active material, the reaction of PTFE with lithium ions leads to side reactions, reducing battery performance. At the same time, the volume expansion of the silicon-based material during charging and discharging leads to the electrode powdering and falling off.
The silicon-based negative electrode material adopts a core-shell structure, the inner core is a silicon-based material, and the outer shell is a crosslinked polymer layer. The crosslinked polymer layer conducts ions but does not conduct electrons, which can block electron tunneling and alleviate the internal stress caused by volume expansion of the silicon-based material.
It effectively inhibits the side reaction between PTFE and lithium ions, improves the first discharge capacity, first effect and cycling performance of the battery, and solves the problems of electrode powdering and shedding caused by volume expansion of silicon-based materials.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery manufacturing technology, and in particular to a silicon-based negative electrode material and a preparation method thereof, a dry electrode, a battery, and an electrical device. Background Art
[0002] The preparation of electrode sheets by wet slurry coating technology has the disadvantages of toxic solvents (such as N-methylpyrrolidone), large investment in solvent recovery, large floor space occupied by the coating oven, and high energy consumption. Based on this, a dry electrode preparation technology is currently used. Specifically, the active material and the conductive agent are dry-mixed evenly by powder extrusion molding, and then the adhesive is added. After the adhesive is fiberized, it is rolled to form a self-supporting film. Finally, the self-supporting film is rolled and covered on the surface of the current collector to obtain a dry electrode sheet. The dry electrode preparation technology does not require the use of solvents, eliminates the electrode drying and solvent recovery steps, has a simpler process flow, and occupies a smaller area of equipment. If mass production is carried out, lower electrode manufacturing costs can be achieved.
[0003] At present, dry electrodes usually use polytetrafluoroethylene (PTFE) as a binder because of its low van der Waals force, loose stacking, and the ability to form a mesh-structured fiber under the action of external shear force, which is used to bond solid powder particles, which is the key to the subsequent preparation of a self-supporting membrane. However, PTFE will react with lithium ions on the surface of the negative electrode to form lithium fluoride, which will weaken the bonding effect and reduce the capacity (single gram of PTFE will consume approximately 1070mAh of lithium, and the higher the PTFE content in the battery, the more lithium will be consumed), thereby affecting the battery performance (such as but not limited to the first discharge capacity, first efficiency, and cycle performance), especially for batteries using silicon-based materials as negative electrode active materials. The volume of silicon-based materials is very easy to expand during the charge and discharge process, which can easily lead to electrode pulverization and shedding, so that the performance of the corresponding battery is further reduced. Summary of the invention
[0004] The purpose of the present application is to provide a silicon-based negative electrode material and a preparation method thereof, a dry electrode, a battery and an electrical device. The silicon-based negative electrode material can effectively inhibit the side reaction of PTFE with lithium ions on the negative electrode surface. At the same time, it can also effectively solve the problems of electrode powdering and falling off caused by volume expansion of the silicon-based material during the charging and discharging process, so that the corresponding battery has a relatively excellent first discharge gram capacity, first efficiency and cycle performance.
[0005] The embodiment of the present application is implemented as follows:
[0006] In a first aspect, an embodiment of the present application provides a silicon-based negative electrode material, which is a core-shell structure, in which the core is a silicon-based material and the shell is a cross-linked polymer layer, and the cross-linked polymer layer can conduct ions but not electrons.
[0007] In the above technical scheme, the silicon-based material is used as the core, and then a cross-linked polymer layer is arranged on its surface, wherein the cross-linked polymer layer has the property of being able to conduct ions but not electrons. On the one hand, this property enables the silicon-based material to normally participate in the charge and discharge cycle of the battery to ensure the normal operation of the battery; on the other hand, it can block electron tunneling and prevent PTFE from being affected by the reduction potential of the silicon-based material, thereby effectively inhibiting the side reaction of PTFE with lithium ions on the negative electrode surface; at the same time, since the cross-linked polymer layer has a three-dimensional network spatial structure, it can effectively alleviate the internal stress generated when the silicon-based material expands in volume, thereby solving the problems of electrode pulverization and shedding caused by volume expansion of the silicon-based material during the charge and discharge process. The silicon-based negative electrode material with a specific structure provided in the present application can simultaneously solve the adverse effects of PTFE as a binder on battery performance and the inherent defects of silicon-based materials when used as negative electrode active materials, so that the corresponding battery has a relatively excellent first discharge gram capacity, first efficiency and cycle performance.
[0008] In some optional embodiments, the silicon-based material includes silicon oxide and graphite, and the mass proportion of silicon oxide in the inner core is 8-12%.
[0009] In the above technical solution, the silicon-based material is set to a combination of silicon oxide and graphite, and the mass proportion of silicon oxide in the core is limited to a specific range, so that the corresponding battery has a higher capacity.
[0010] In some alternative embodiments, the cross-linked polymer layer has carboxylate groups.
[0011] In a second aspect, an embodiment of the present application provides a method for preparing a silicon-based negative electrode material, comprising the following steps:
[0012] A first polymer and a second polymer are added into water and mixed to obtain a polymer solution; wherein the first polymer is polyamic acid, and the second polymer is selected from at least one of carboxymethyl cellulose, polyvinyl alcohol and polyethyleneimine; a silicon-based material is added into the polymer solution and mixed to obtain a mixed solution; the mixed solution is subjected to a first heat treatment until all water in the mixed solution is volatilized to obtain a silicon-based negative electrode material precursor; the silicon-based negative electrode material precursor is subjected to a second heat treatment under vacuum conditions, so that the first polymer and the second polymer undergo a cross-linking reaction on the surface of the silicon-based material to form a silicon-based negative electrode material with a core-shell structure.
[0013] In the above technical solution, a silicon-based negative electrode material with a cross-linked polymer layer on the surface can be prepared according to a specific process, wherein the cross-linked polymer layer has the characteristics of being able to conduct ions but not electrons, and can effectively inhibit the side reaction of PTFE with lithium ions on the negative electrode surface; in addition, the cross-linked polymer layer also has a three-dimensional network space structure, which can effectively solve the problems of electrode pulverization and shedding caused by volume expansion of silicon-based materials during charging and discharging. Because the silicon-based negative electrode material with this specific structure can simultaneously solve the adverse effects of PTFE as a binder on battery performance and the inherent defects of silicon-based materials when used as negative electrode active materials, the corresponding battery has relatively excellent first discharge gram capacity, first efficiency and cycle performance.
[0014] In some optional embodiments, in the mixed solution, the mass ratio of the silicon-based material to the polymer is (95-96.5): (0.5-2).
[0015] In the above technical scheme, the mass ratio of the silicon-based material to the polymer (the sum of the masses of the first polymer and the second polymer) in the mixed solution is limited to a specific range, so that the formed cross-linked polymer layer has an appropriate thickness, so as to better balance the properties of ion conductivity and electron blocking (if the coating layer is too thick, the ion conductivity is poor; if the coating layer is too thin, the electron blocking performance is poor); at the same time, the cross-linked polymer layer can also have a richer three-dimensional network structure, so that it can more effectively alleviate the internal stress generated by the silicon-based material during volume expansion, thereby more effectively solving the problems of electrode powdering and falling off caused by volume expansion of the silicon-based material during the charging and discharging process.
[0016] In some alternative embodiments, the first polymer is polyamic acid and the second polymer is carboxymethyl cellulose.
[0017] In the above technical solution, carboxymethyl cellulose is used as the second polymer because it has relatively excellent electrochemical stability, which is more helpful to improve the first discharge capacity, first efficiency and cycle performance of the corresponding battery.
[0018] In some optional embodiments, in the polymer solution, the mass ratio of the first polymer to the second polymer is 1:(0.8-1.2).
[0019] In the above technical solution, the mass ratio of the first polymer to the second polymer in the polymer solution is limited to a specific range so that the two have an appropriate mass ratio, thereby facilitating the formation of a cross-linked polymer layer.
[0020] In some optional embodiments, the solid content of the polymer solution is 1-5%.
[0021] In the above technical solution, the solid content in the polymer solution is limited to a specific range so that the polymer solution has an appropriate concentration, which helps to improve the coating uniformity and prepare a cross-linked polymer layer with good coating integrity and uniform thickness.
[0022] In some optional embodiments, in the second heat treatment step, the treatment temperature is 120-180° C., and the treatment time is 0.5-6 h.
[0023] In the above technical solution, the treatment temperature and treatment time in the second heat treatment step are respectively limited within specific ranges to provide more suitable cross-linking conditions, thereby facilitating the formation of a cross-linked polymer layer.
[0024] In a third aspect, an embodiment of the present application provides a dry electrode, comprising a current collector and an electrode film located on one side or both sides of the current collector, the electrode film comprising a silicon-based negative electrode material as provided in the embodiment of the first aspect or a silicon-based negative electrode material prepared by the preparation method of the silicon-based negative electrode material as provided in the embodiment of the second aspect, a conductive agent and polytetrafluoroethylene.
[0025] In the above technical solution, the electrode film in the dry electrode includes the silicon-based negative electrode material provided in the first embodiment or the silicon-based negative electrode material prepared by the preparation method of the silicon-based negative electrode material provided in the second embodiment. The cross-linked polymer layer on the surface of the silicon-based negative electrode material has the property of being able to conduct ions but not electrons, and can effectively inhibit the side reaction of PTFE with lithium ions on the negative electrode surface. In addition, the cross-linked polymer layer also has a three-dimensional network space structure, which can effectively solve the problems of electrode powderization and shedding caused by volume expansion of silicon-based materials during charging and discharging. Because the silicon-based negative electrode material with this specific structure can simultaneously solve the adverse effects of PTFE as a binder on battery performance and the inherent defects of silicon-based materials when used as negative electrode active materials, the corresponding battery has a relatively excellent first discharge gram capacity, first efficiency and cycle performance.
[0026] In some optional embodiments, the mass ratio of the silicon-based negative electrode material in the electrode film is 96-98%, and / or the mass ratio of the conductive agent to polytetrafluoroethylene is (1.5-2.5): (0.5-1.5).
[0027] In the above technical solution, the mass proportion of the silicon-based negative electrode material in the electrode film and the mass ratio of the conductive agent and polytetrafluoroethylene are respectively limited within specific ranges, so that the prepared electrode film has relatively excellent comprehensive electrical properties.
[0028] In some optional embodiments, the thickness of the single-layer electrode film is 60-160 μm.
[0029] In the above technical solution, the thickness of the single-layer electrode film is limited to a specific range so that it has a relatively ideal compaction density and surface density, thereby making the corresponding battery have a relatively ideal comprehensive electrical performance.
[0030] In some optional embodiments, the weight average molecular weight of polytetrafluoroethylene is 4×10 7 ~8×10 7 .
[0031] In the above technical solution, polytetrafluoroethylene with a specific weight average molecular weight is used, which has the advantages of good bonding effect and fiberization effect.
[0032] In some optional embodiments, the current collector is a carbon-coated copper foil, and the thickness of the current collector is 5 to 10 μm.
[0033] In the above technical solution, carbon-coated copper foil is used as the current collector, which is more conducive to the preparation of dry electrodes; in addition, the thickness of the current collector is further limited to a specific range so that it has a more suitable strength, so that it can better load and support the electrode film.
[0034] In a fourth aspect, an embodiment of the present application provides a battery, comprising a dry electrode provided in the embodiment of the third aspect.
[0035] In a fifth aspect, an embodiment of the present application provides an electrical device, comprising a battery as provided in the embodiment of the fourth aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1 A schematic cross-sectional view of a silicon-based negative electrode material provided in an embodiment of the present application;
[0038] Figure 2 A process flow chart of a method for preparing a silicon-based negative electrode material provided in an embodiment of the present application.
[0039] Icon: 10-silicon-based negative electrode material; 100-core; 200-shell. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0041] It should be noted that “and / or” in this application, such as “Feature 1 and / or Feature 2”, refers to the three situations of “Feature 1” alone, “Feature 2” alone, or “Feature 1” plus “Feature 2”.
[0042] In addition, in the description of the present application, unless otherwise specified, the meaning of "multiple" in "one or more" refers to two or more; the range of "value a ~ value b" includes the two end values "a" and "b", and the "unit" in "value a ~ value b + unit of measurement" represents the "unit of measurement" of both "value a" and "value b".
[0043] The silicon-based negative electrode material and its preparation method, dry electrode, battery and electrical equipment in the embodiments of the present application are described in detail below.
[0044] See also Figure 1 In the first aspect, an embodiment of the present application provides a silicon-based negative electrode material 10, which is a core-shell structure, in which the core 100 is a silicon-based material, and the outer shell 200 is a cross-linked polymer layer, and the cross-linked polymer layer can conduct ions but not electrons.
[0045] In the present application, the silicon-based material is used as the core 100, and then a cross-linked polymer layer is arranged on its surface, wherein the cross-linked polymer layer has the property of being able to conduct ions but not electrons, which, on the one hand, enables the silicon-based material to normally participate in the charge and discharge cycle of the battery and ensure the normal operation of the battery; on the other hand, it can block electron tunneling and prevent PTFE from being affected by the reduction potential of the silicon-based material, thereby effectively inhibiting the side reaction of PTFE with lithium ions on the negative electrode surface; at the same time, since the cross-linked polymer layer has a three-dimensional mesh spatial structure, it can effectively alleviate the internal stress generated when the silicon-based material expands in volume, thereby solving the problems of electrode pulverization and shedding caused by volume expansion of the silicon-based material during the charge and discharge process. The silicon-based negative electrode material 10 with a specific structure provided in the present application can simultaneously solve the adverse effects of PTFE as a binder on battery performance and the inherent defects of silicon-based materials when used as negative electrode active materials, so that the corresponding battery has a relatively excellent first discharge gram capacity, first efficiency and cycle performance.
[0046] It should be noted that the solution for coating and modifying silicon-based materials provided in the embodiment of the present application, compared with the solution for coating and modifying PTFE in the prior art, will not affect the bonding effect and subsequent fiberization effect of PTFE, so that the corresponding battery can have better comprehensive electrical performance.
[0047] As an example, the silicon-based material includes silicon oxide and graphite, and the mass proportion of silicon oxide in the core is 8-12%, for example but not limited to any point value among 8%, 9%, 10%, 11% and 12% or a range value between any two of them.
[0048] In this embodiment, the silicon-based material is set to a combination of silicon oxide and graphite, and the mass proportion of silicon oxide in the core is limited to a specific range, so that the corresponding battery has a higher capacity.
[0049] It should be noted that the silicon monoxide in the silicon-based material can also be partially or completely replaced by silicon oxide.
[0050] It should be noted that in the present application, the mass proportion of silicon iodide in the core can be as high as 8-12%, largely because the presence of the cross-linked polymer layer can effectively solve the problem of poor electrode properties caused by silicon-based volume expansion.
[0051] As an example, the cross-linked polymer layer has carboxylate groups.
[0052] In a second aspect, an embodiment of the present application provides a method for preparing a silicon-based negative electrode material, comprising the following steps:
[0053] A first polymer and a second polymer are added into water and mixed to obtain a polymer solution; wherein the first polymer is polyamic acid, and the second polymer is selected from at least one of carboxymethyl cellulose, polyvinyl alcohol and polyethyleneimine; a silicon-based material is added into the polymer solution and mixed to obtain a mixed solution; the mixed solution is subjected to a first heat treatment until all water in the mixed solution is volatilized to obtain a silicon-based negative electrode material precursor; the silicon-based negative electrode material precursor is subjected to a second heat treatment under vacuum conditions, so that the first polymer and the second polymer undergo a cross-linking reaction on the surface of the silicon-based material to form a silicon-based negative electrode material with a core-shell structure.
[0054] In the present application, a silicon-based negative electrode material with a cross-linked polymer layer on the surface can be prepared according to a specific process, wherein the cross-linked polymer layer has the property of being able to conduct ions but not electrons, and can effectively inhibit the side reaction of PTFE with lithium ions on the negative electrode surface; in addition, the cross-linked polymer layer also has a three-dimensional network space structure, which can effectively solve the problems of electrode pulverization and shedding caused by volume expansion of silicon-based materials during charging and discharging. Because the silicon-based negative electrode material with this specific structure can simultaneously solve the adverse effects of PTFE as a binder on battery performance and the inherent defects of silicon-based materials when used as negative electrode active materials, the corresponding battery has relatively excellent first discharge gram capacity, first efficiency and cycle performance.
[0055] It should be noted that the ion-conducting but electron-non-conducting properties of the cross-linked polymer layer and the richness of the three-dimensional network structure are closely related to its thickness. Based on this, the parameters related to the coating thickness can be defined.
[0056] As an example, in the mixed solution, the mass ratio of silicon-based material to polymer is (95-96.5):(0.5-2), for example but not limited to the mass ratio of any one of 95:2, 96:1 and 96.5:0.5 or a range between any two of them.
[0057] In this embodiment, the mass ratio of the silicon-based material to the polymer (the sum of the masses of the first polymer and the second polymer) in the mixed solution is limited to a specific range, so that the formed cross-linked polymer layer has an appropriate thickness, thereby being able to better balance the properties of ion conductivity and electron blocking (if the coating layer is too thick, the ion conductivity is poor; if the coating layer is too thin, the electron blocking performance is poor); at the same time, the cross-linked polymer layer can also have a richer three-dimensional network structure, so that it can more effectively relieve the internal stress generated by the silicon-based material during volume expansion, thereby more effectively solving the problems of electrode powdering and falling off caused by volume expansion of the silicon-based material during the charging and discharging process.
[0058] As an example, the first polymer is polyamic acid, and the second polymer is carboxymethyl cellulose.
[0059] In this embodiment, carboxymethyl cellulose is used as the second polymer because it has relatively excellent electrochemical stability, which is more helpful to improve the first discharge capacity, first efficiency and cycle performance of the corresponding battery.
[0060] As an example, in the polymer solution, the mass ratio of the first polymer to the second polymer is 1:(0.8-1.2), for example but not limited to, the mass ratio of the two is any one of 1:0.8, 1:0.9, 1:1, 1:1.1 and 1:1.2 or a range between any two of them.
[0061] In this embodiment, the mass ratio of the first polymer to the second polymer in the polymer solution is limited to a specific range so that the two have an appropriate mass ratio, thereby facilitating the formation of a cross-linked polymer layer.
[0062] As an example, the solid content in the polymer solution is 1-5%, for example but not limited to any point value among 1%, 2%, 3%, 4% and 5%, or a range between any two of the solid content.
[0063] In this embodiment, the solid content in the polymer solution is limited to a specific range so that the polymer solution has a suitable concentration, which helps to improve the coating uniformity and prepare a cross-linked polymer layer with good coating integrity and uniform thickness.
[0064] As an example, in the second heat treatment step, the treatment temperature is 120-180°C, for example but not limited to the treatment temperature is any one of 120°C, 130°C, 140°C, 150°C, 160°C, 170°C and 180°C, or a range between any two of them; the treatment time is 0.5-6h, for example but not limited to the treatment time is any one of 0.5h, 1h, 2h, 3h, 4h, 5h and 6h, or a range between any two of them.
[0065] In this embodiment, the treatment temperature and treatment time in the second heat treatment step are respectively limited to specific ranges to provide more suitable cross-linking conditions, thereby facilitating the formation of a cross-linked polymer layer.
[0066] It should be noted that any process or step not specifically described or limited in the preparation of silicon-based negative electrode materials may be arranged according to conventional selection in the art.
[0067] As an example, in the step of adding the silicon-based material to the polymer solution and mixing, the stirring speed is 100 to 1000 rpm, for example but not limited to, the stirring speed is any one of 100 rpm, 200 rpm, 400 rpm, 600 rpm, 800 rpm and 1000 rpm or a range between any two of them.
[0068] As an example, the process flow chart of the preparation method of silicon-based negative electrode material is exemplified by referring to Figure 2 .
[0069] In a third aspect, an embodiment of the present application provides a dry electrode, comprising a current collector and an electrode film located on one side or both sides of the current collector, the electrode film comprising a silicon-based negative electrode material as provided in the embodiment of the first aspect or a silicon-based negative electrode material prepared by the preparation method of the silicon-based negative electrode material as provided in the embodiment of the second aspect, a conductive agent and polytetrafluoroethylene.
[0070] In the present application, the electrode film in the dry electrode includes a silicon-based negative electrode material as provided in the first embodiment or a silicon-based negative electrode material prepared by the method for preparing the silicon-based negative electrode material as provided in the second embodiment. The cross-linked polymer layer on the surface of the silicon-based negative electrode material has the property of being able to conduct ions but not electrons, and can effectively inhibit the side reaction of PTFE with lithium ions on the negative electrode surface. In addition, the cross-linked polymer layer also has a three-dimensional network space structure, which can effectively solve the problems of electrode powderization and shedding caused by volume expansion of the silicon-based material during the charging and discharging process. Due to the silicon-based negative electrode material of this specific structure, it can simultaneously solve the adverse effects of PTFE as a binder on battery performance and the inherent defects of silicon-based materials when used as negative electrode active materials, so that the corresponding battery has a relatively excellent first discharge gram capacity, first efficiency and cycle performance.
[0071] As an example, the mass proportion of silicon-based negative electrode material in the electrode film is 96-98%, for example but not limited to the mass proportion of 96%, 96.5%, 97%, 97.5% and 98% or any point value or a range value between any two of them; and / or, the mass ratio of the conductive agent and polytetrafluoroethylene is (1.5-2.5): (0.5-1.5), for example but not limited to the mass ratio of 1.5:1.5, 2:1 and 2.5:0.5 or any point value or a range value between any two of them.
[0072] In this embodiment, the mass proportion of the silicon-based negative electrode material in the electrode film and the mass ratio of the conductive agent to polytetrafluoroethylene are respectively limited within specific ranges, so that the prepared electrode film has relatively excellent comprehensive electrical properties.
[0073] As an example, the thickness of the single-layer electrode film is 60-160 μm, for example but not limited to any one of 60 μm, 80 μm, 100 μm, 120 μm and 160 μm or a range between any two of the thicknesses.
[0074] In this embodiment, the thickness of the single-layer electrode film is limited to a specific range so that it has a relatively ideal compaction density and surface density, thereby making the corresponding battery have a relatively ideal comprehensive electrical performance.
[0075] As an example, the weight average molecular weight of polytetrafluoroethylene is 4×10 7 ~8×10 7 , for example but not limited to a weight average molecular weight of 4×10 7 , 5×10 7 , 6×10 7 ,7×10 7 and 8×10 7 Any point value in or any range of values between them.
[0076] In this embodiment, polytetrafluoroethylene with a specific weight average molecular weight is used, which has the advantages of good bonding effect and fiberization effect.
[0077] As an example, the current collector is a carbon-coated copper foil, and the thickness of the current collector is 5 to 10 μm, for example but not limited to any one of 5 μm, 6 μm, 7 μm, 8 μm, 9 μm and 10 μm or a range between any two of the thicknesses.
[0078] In this embodiment, carbon-coated copper foil is used as the current collector, which is more conducive to the preparation of dry electrodes; in addition, the thickness of the current collector is further limited to a specific range so that it has a more suitable strength, so that it can better load and support the electrode film.
[0079] It should be noted that any structure not specifically described or limited in the dry electrode may be configured according to conventional selections in the art.
[0080] As an example, the conductive agent is selected from at least one of carbon nanotubes and conductive carbon black.
[0081] It should be noted that the preparation method of the dry electrode can be set according to the conventional selection in the art.
[0082] As an example, the preparation method of the dry electrode includes the following steps: adding the silicon-based negative electrode material, the conductive agent and the PTFE according to the mass ratio into the powder equipment for dry mixing to obtain a uniformly dispersed composite material; adding the composite material into the air flow mill equipment for further dispersion of the composite material and fiberization of the binder; rolling the fiberized material through a roller press to obtain a self-supporting electrode film, and finally rolling the self-supporting electrode film together with the foil material to roll the two together to obtain a dry electrode.
[0083] As an example, in the process of rolling the fiberized material through a roller press to obtain a self-supporting electrode film, the processing temperature of the roller press is 50-150°C, for example but not limited to the processing temperature of any point value among 50°C, 80°C, 100°C, 120°C and 150°C or a range value between any two of them.
[0084] In a fourth aspect, an embodiment of the present application provides a battery, comprising a dry electrode provided in the embodiment of the third aspect.
[0085] It should be noted that any structural or functional unit not specifically described in the battery may be configured according to conventional selections in the art.
[0086] In a fifth aspect, an embodiment of the present application provides an electrical device, comprising a battery as provided in the embodiment of the fourth aspect.
[0087] It should be noted that there is no limitation on the types of electrical equipment, such as mobile phones, portable devices, laptops, electric vehicles, electric cars, ships, spacecraft, electric toys, energy storage devices and electric tools.
[0088] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0089] Example 1
[0090] (1) Preparation of silicon-based negative electrode materials
[0091] The first polymer (polyamic acid) and the second polymer (carboxymethyl cellulose) are added to water and stirred to obtain a polymer solution; wherein the mass ratio of polyamic acid to carboxymethyl cellulose is 1:1, and the solid content in the polymer solution is 3%. A silicon-based material (a mixture of 10wt% silicon dioxide and 90wt% graphite) is added to the polymer solution and stirred and mixed for 3h at room temperature (25°C) to obtain a mixed solution; wherein the mass ratio of silicon-based material to polymer is 96:1, and the stirring speed is 500rpm. The mixed solution is heat-treated at 100°C until all the water in the mixed solution is volatilized to obtain a silicon-based negative electrode material precursor. The silicon-based negative electrode material precursor is placed in a vacuum condition for a second heat treatment (treatment temperature is 160°C, treatment time is 3h), so that polyamic acid and carboxymethyl cellulose undergo a cross-linking reaction on the surface of the silicon-based material to form a silicon-based negative electrode material with a core-shell structure.
[0092] (2) Dry electrode preparation
[0093] The silicon-based negative electrode material, the conductive agent and PTFE were added into the powder equipment in a mass ratio of 97:1.5:1.5 for dry mixing to obtain a uniformly dispersed composite material; wherein the conductive agent was carbon nanotubes, and the weight average molecular weight of PTFE was 6×10 7 The composite material is added into the air flow mill to further disperse the composite material and fiberize the binder; the fiberized material is rolled by a roller press (processing temperature is 100°C) to obtain a self-supporting electrode film with a thickness of 100 μm, and finally the self-supporting electrode film is rolled together with a carbon-coated copper foil (thickness is 10 μm) to roll the self-supporting electrode film and the single-sided carbon-coated copper foil together to obtain a dry electrode.
[0094] Example 2
[0095] The embodiment of the present application provides a method for preparing a dry electrode, which differs from Embodiment 1 only in that in step (1), the mass ratio of the silicon-based material to the polymer is 95:2.
[0096] Example 3
[0097] The embodiment of the present application provides a method for preparing a dry electrode, which differs from Embodiment 1 only in that: in step (1), the mass ratio of the silicon-based material to the polymer is 96.5:0.5.
[0098] Example 4
[0099] The embodiment of the present application provides a method for preparing a dry electrode, which differs from Embodiment 1 only in that in step (1), the mass ratio of the silicon-based material to the polymer is 94:3.
[0100] Example 5
[0101] The embodiment of the present application provides a method for preparing a dry electrode, which differs from Embodiment 1 only in that: in step (1), the mass ratio of the silicon-based material to the polymer is 96.8:0.2.
[0102] Example 6
[0103] The present application embodiment provides a method for preparing a dry electrode, which differs from Example 1 only in that: a first polymer (polyamic acid) and a second polymer (polyvinyl alcohol) are added to water and stirred to obtain a polymer solution; wherein the mass ratio of polyamic acid to carboxymethyl cellulose is 1:1, and the solid content in the polymer solution is 3%. A silicon-based material (a mixture of 10wt% silicon dioxide and 90wt% graphite) is added to the polymer solution and stirred and mixed for 3h at room temperature (25°C) to obtain a mixed solution; wherein the mass ratio of silicon-based material to polymer is 96:1, and the stirring speed is 500rpm. The mixed solution is heat-treated at 100°C until all the water in the mixed solution is volatilized to obtain a silicon-based negative electrode material precursor. The silicon-based negative electrode material precursor is placed under vacuum conditions for a second heat treatment (treatment temperature is 160°C, treatment time is 3h), so that polyamic acid and carboxymethyl cellulose undergo a cross-linking reaction on the surface of the silicon-based material to form a silicon-based negative electrode material with a core-shell structure.
[0104] Comparative Example 1
[0105] The comparative example of the present application provides a method for preparing a dry electrode, comprising the following steps:
[0106] The uncoated silicon-based material, the conductive agent and PTFE were added into the powder equipment in a mass ratio of 97:1.5:1.5 for dry mixing to obtain a uniformly dispersed composite material; wherein the conductive agent was carbon nanotubes, and the weight average molecular weight of PTFE was 6×10 7The composite material is added into the air flow mill to further disperse the composite material and fiberize the binder; the fiberized material is rolled by a roller press (processing temperature is 100°C) to obtain a self-supporting electrode film with a thickness of 100 μm, and finally the self-supporting electrode film is rolled together with a carbon-coated copper foil (thickness is 10 μm) to roll the self-supporting electrode film and the single-sided carbon-coated copper foil together to obtain a dry electrode.
[0107] Comparative Example 2
[0108] The comparative example of the present application provides a method for preparing a dry electrode, comprising the following steps:
[0109] Add the polymer (polyamic acid) to water and stir to obtain a polymer solution; the solid content in the polymer solution is 3%. Add the silicon-based material (a mixture of 10wt% silicon dioxide and 90wt% graphite) to the polymer solution and stir to obtain a mixed solution at room temperature (25°C) for 3 hours; wherein the mass ratio of the silicon-based material to the polymer is 96:1, and the stirring speed is 500rpm. The mixed solution is heat-treated at 100°C until all the water in the mixed solution is volatilized to obtain a silicon-based negative electrode material precursor. The silicon-based negative electrode material precursor is placed in a vacuum condition for a second heat treatment (treatment temperature of 160°C, treatment time of 3h), so that the polyamic acid and carboxymethyl cellulose undergo a cross-linking reaction on the surface of the silicon-based material to form a silicon-based negative electrode material with a core-shell structure.
[0110] Comparative Example 1
[0111] The comparative example of the present application adopts conventional wet slurry coating technology to prepare the electrode.
[0112] Test example
[0113] Electrical performance test of electrodes
[0114] Test method:
[0115] The dry electrodes (i.e., positive electrodes) prepared in Examples 1 to 6, Comparative Examples 1 to 2, and Control Example 1 were assembled into lithium secondary ion batteries and numbered accordingly, and then the first discharge capacity in grams, first efficiency, and cycle performance of each lithium secondary battery were tested.
[0116] The lithium secondary battery is assembled as follows:
[0117] S1 is mixed with LiNi in a mass ratio of 96.8:2.0:1.2 0.8 Co 0.1 Mn 0.1O2 (positive electrode active material), conductive carbon black (conductive agent) and polyvinylidene fluoride (binder) are dispersed in N-methyl-2-pyrrolidone to obtain positive electrode slurry; then, the positive electrode slurry is evenly coated on both sides of the aluminum foil; then, after drying, calendering and vacuum drying in sequence, an aluminum lead wire is welded with an ultrasonic welder to obtain a positive electrode sheet with a thickness of 125μm.
[0118] S2 stacks the prepared dry electrode (i.e., negative electrode sheet), separator (PE-coated ceramic separator, thickness 14 μm) and positive electrode sheet in sequence and winds them to obtain a bare cell. Then, the bare cell is injected with electrolyte (wherein the electrolyte composition is 1 mol / L LiPF6 / EC+DMC+EMC+FEC (volume ratio 1:1:1:0.1), packaged, allowed to stand, formed, shaped and capacity tested to obtain a lithium secondary battery.
[0119] The test steps for the first discharge capacity are as follows:
[0120] At 25°C, the battery is charged to 4.25V at a constant current of 0.33C, then charged at a constant voltage until the current is less than or equal to 0.05C, then left to stand for 5 minutes, and then discharged to 2.8V at a constant current of 0.33C, then left to stand for 5 minutes. This is a charge and discharge cycle, and the discharge capacity is recorded as the discharge capacity of the first cycle of the battery. Discharge gram capacity = discharge capacity / mass of active material.
[0121] The first-effect test steps are as follows:
[0122] At 25°C, the battery is charged to 4.25V at a constant current of 0.33C, then charged at a constant voltage until the current is less than or equal to 0.05C, then left to stand for 5 minutes, and then discharged to 2.8V at a constant current of 0.33C, then left to stand for 5 minutes. This is a charge and discharge cycle, and the charge and discharge capacity of this time is recorded as the first charge and discharge capacity. First efficiency (first coulomb efficiency) = first discharge capacity / first charge capacity × 100%.
[0123] The test steps for cycle performance are as follows:
[0124] At 25°C, the battery is charged to 4.25V at 1C constant current, then charged at constant voltage until the current is less than or equal to 0.05C, then left to stand for 5 minutes, and then discharged to 2.8V at 1C constant current, then left to stand for 5 minutes. This is a charge and discharge cycle. The battery cell is tested for multiple cycles of charge and discharge in the above manner, and the charge and discharge capacity of the 500th cycle is detected, and the capacity retention rate of the battery cell after the cycle is calculated by the following formula. Capacity retention rate of the battery after 500 cycles (%) = [discharge capacity of the 500th cycle / discharge capacity of the 1st cycle] × 100%.
[0125] Table 1 Electrical performance statistics
[0126]
[0127] Referring to Table 1, it can be seen from the test results of Example 1, Comparative Example 1 and Control Example 1 that the graphite negative electrode material provided in the embodiment of the present application has a polymer coating layer that conducts ions but does not conduct electrons on the surface. Compared with the existing graphite that has not been coated and modified, the battery corresponding to the former can effectively inhibit the side reaction of PTFE with lithium ions on the negative electrode surface; at the same time, the cross-linked polymer layer formed has a three-dimensional network space structure, which can effectively alleviate the internal stress generated when the silicon-based material expands in volume, thereby solving the problems of electrode pulverization and shedding caused by volume expansion of the silicon-based material during the charging and discharging process. The silicon-based negative electrode material with a specific structure provided in the present application can simultaneously solve the adverse effects of PTFE as a binder on battery performance and the inherent defects of silicon-based materials when used as negative electrode active materials, so that the corresponding battery has relatively excellent first discharge gram capacity, first efficiency and cycle performance, and the first discharge gram capacity and first efficiency are comparable to the performance of the battery prepared by the wet slurry coating technology.
[0128] In particular, the cycle performance of Example 1 is better than that of Comparative Example 1. This is due to the presence of the cross-linked polymer layer, which can effectively alleviate the internal stress generated when the silicon-based material expands in volume, thereby solving the problems of electrode pulverization and shedding caused by volume expansion of the silicon-based material during the charging and discharging process.
[0129] It can be seen from the test results of Example 1 and Comparative Example 2 that when a single polymer is used to coat the silicon-based material, it is difficult to effectively relieve the internal stress generated when the silicon-based material expands in volume, because a cross-linked polymer layer cannot be formed, resulting in poor cycle performance of the corresponding battery.
[0130] It can be seen from the test results of Examples 1 to 3 and Examples 4 to 5 that in the process of preparing silicon-based negative electrode materials, the mass ratio of silicon-based materials and polymers is limited within a specific range so that the coating layer has an appropriate thickness. Compared with the mass ratio of silicon-based materials and polymers not being within the limited range, the cross-linked polymer layer formed by the former can better balance the properties of ion conduction and electron blocking and has a richer three-dimensional network spatial structure, so that the corresponding battery has a better first discharge capacity per gram, first efficiency and cycle performance.
[0131] It can be seen from the test results of Example 1 and Example 5 that the battery prepared by using a polymer with better electrochemical stability as the coating material has better first discharge capacity per gram, first efficiency and cycle performance.
[0132] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
Claims
1. A silicon-based negative electrode material, characterized in that: The silicon-based negative electrode material is a core-shell structure, wherein the core is a silicon-based material and the shell is a cross-linked polymer layer, and the cross-linked polymer layer can conduct ions but cannot conduct electrons.
2. The silicon-based negative electrode material according to claim 1, characterized in that: The silicon-based material includes silicon oxide and graphite, and the mass proportion of silicon oxide in the core is 8-12%.
3. The silicon-based negative electrode material according to claim 1, characterized in that: The cross-linked polymer layer has carboxylate groups.
4. A method for preparing a silicon-based negative electrode material, characterized in that: The following steps are involved: Adding a first polymer and a second polymer into water and mixing them to obtain a polymer solution; wherein the first polymer is polyamic acid, and the second polymer is selected from at least one of carboxymethyl cellulose, polyvinyl alcohol and polyethyleneimine; adding a silicon-based material to the polymer solution and mixing the mixture to obtain a mixed solution; Performing a first heat treatment on the mixed solution until all the water in the mixed solution is volatilized to obtain a silicon-based negative electrode material precursor; The silicon-based negative electrode material precursor is placed under vacuum conditions for a second heat treatment, so that the first polymer and the second polymer undergo a cross-linking reaction on the surface of the silicon-based material to form a silicon-based negative electrode material with a core-shell structure.
5. The method for preparing a silicon-based negative electrode material according to claim 4, characterized in that: In the mixed solution, the mass ratio of the silicon-based material to the polymer is (95-96.5):(0.5-2).
6. The method for preparing a silicon-based negative electrode material according to claim 4, characterized in that: The first polymer is the polyamic acid, and the second polymer is the carboxymethyl cellulose.
7. The method for preparing a silicon-based negative electrode material according to claim 4, characterized in that: In the polymer solution, the mass ratio of the first polymer to the second polymer is 1:(0.8-1.2).
8. The method for preparing a silicon-based negative electrode material according to claim 4, characterized in that: The solid content of the polymer solution is 1-5%.
9. The method for preparing a silicon-based negative electrode material according to claim 4, characterized in that: In the second heat treatment step, the treatment temperature is 120-180° C. and the treatment time is 0.5-6 hours.
10. A dry electrode, characterized in that: It comprises a current collector and an electrode film located on one side or both sides of the current collector, wherein the electrode film comprises the silicon-based negative electrode material as described in any one of claims 1 to 3 or the silicon-based negative electrode material prepared by the preparation method of the silicon-based negative electrode material as described in any one of claims 4 to 9, a conductive agent and polytetrafluoroethylene.
11. The dry electrode according to claim 10, characterized in that: The mass ratio of the silicon-based negative electrode material in the electrode film is 96-98%, and / or the mass ratio of the conductive agent to the polytetrafluoroethylene is (1.5-2.5): (0.5-1.5).
12. The dry electrode according to claim 10, characterized in that: The thickness of a single-layer electrode film is 60 to 160 μm.
13. The dry electrode according to claim 10, characterized in that: The weight average molecular weight of the polytetrafluoroethylene is 4×10 7 ~8×10 7 .
14. The dry electrode according to claim 10, characterized in that: The current collector is a carbon-coated copper foil, and the thickness of the current collector is 5 to 10 μm.
15. A battery, characterized in that: It comprises the dry electrode according to any one of claims 10 to 14.
16. An electrical equipment, characterized in that: Comprising the battery of claim 15.
Citation Information
Cited By
Battery negative electrode, secondary battery, negative electrode material and preparation method of negative electrode material
CN120545327A
Negative electrode composite material adapted to dry electrode process, preparation method, and use
WO2026194155A1